Fundamentals of geobiology - Knoll, Andrew H.; Canfield, Donald E.; Konhauser, Kurt. (Chichester, West Sussex ; Hoboken, NJ : John Wiley & Sons, 2012)
For more than fifty years scientists have been concerned with the interrelationships of Earth and life. Over the past decade, however, geobiology, the name given to this interdisciplinary endeavour, has emerged as an exciting and rapidly expanding field, fuelled by advances in molecular phylogeny, a new microbial ecology made possible by the molecular revolution, increasingly sophisticated new techniques for imaging and determining chemical compositions of solids on nanometer scales, the development of non-traditional stable isotope analyses, Earth systems science and Earth system history, and accelerating exploration of other planets within and beyond our solar system. Geobiology has many faces: there is the microbial weathering of minerals, bacterial and skeletal biomineralization, the roles of autotrophic and heterotrophic metabolisms in elemental cycling, the redox history in the oceans and its relationship to evolution and the origin of life itself. This book is the first to set out a coherent set of principles that underpin geobiology, and will act as a foundational text that will speed the dissemination of those principles. The chapters have been carefully chosen to provide intellectually rich but concise summaries of key topics, and each has been written by one or more of the leading scientists in that field. Fundamentals of Geobiology is aimed at advanced undergraduates and graduates in the Earth and biological sciences, and to the growing number of scientists worldwide who have an interest in this burgeoning new discipline.
1. What is geobiology? / Andrew H Knoll, Donald E Canfield, and Kurt O Konhauser -- 2. The global carbon cycle: biological processes / Paul G Falkowski -- 2. The global carbon cycle: geological processes / Klaus Wallmann and Giovanni Aloisi -- 4. The global nitrogen cycle / Bess Ward -- 5. The global sulfur cycle / Donald E Canfield and James Farquhar -- 6. The global iron cycle / Brian Kendall, Ariel D Anbar, Andreas Kappler and Kurt O Konhauser -- 7. The global oxygen cycle / James F Kasting and Donald E Canfield -- 8. Bacterial biomineralization / Kurt Konhauser and Robert Riding -- 9. Mineral-organic-microbe interfacial chemistry / David J Vaughan and Jonathan R Lloyd -- 10. Eukaryotic skeletal formation / Adam F Wallace, Dongbo Wang, Laura M Hamm, Andrew H Knoll and Patricia M Dove -- 11. Plants and animals as geobiological agents / David J Beerling and Nicholas J Butterfield -- 12. A geobiological view of weathering and erosion / Susan L Brantley, Marina Lebedeva and Elisabeth M Hausrath -- 13. Molecular biology's contributions to geobiology / Dianne K Newman, Victoria J Orphan and Anna-Louise Reysenbach -- 14. Stable isotope geobiology / D T Johnston and W W Fischer -- 15. Biomarkers: informative molecules for studies in geobiology / Roger E Summons and Sara A Lincoln -- 16. The fossil record of microbial life / Andrew H Knoll -- 17. Geochemical origins of life / Robert M Hazen -- 18. Mineralogical co-evolution of the geosphere and biosphere / Robert M Hazen and Dominic Papineau -- 19. Geobiology of the Archean Eon / Roger Buick -- 20. Geobiology of the Proterozoic Eon / Timothy W Lyons, Christopher T Reinhard, Gordon D Love and Shuhai Xiao -- 21. Geobiology of the Phanerozoic / Steven M Stanley -- 22. Geobiology of the Anthropocene / Daniel P Schrag.
Includes bibliographical references and index.
Print version record.
Keywords: Geobiology; NATURE -- Ecology; NATURE -- Ecosystems & Habitats -- Wilderness; SCIENCE -- Environmental Science; SCIENCE -- Life Sciences -- Ecology; Geobiology; Electronic books